A genomically modified Escherichia coli strain carrying an orthogonal E. coli histidyl-tRNA synthetase•tRNA His pair - Englert, Markus; Vargas-Rodriguez, Oscar; Reynolds, Noah M.; Wang, Yane-Shih; Söll, Dieter; Umehara, Takuya (Biochimica et biophysica acta. General subjects, 2017)
Development of new aminoacyl-tRNA synthetase (aaRS)•tRNA pairs is central for incorporation of novel non-canonical amino acids (ncAAs) into proteins via genetic code expansion (GCE). The Escherichia coli and Caulobacter crescentus histidyl-tRNA synthetases (HisRS) evolved divergent mechanisms of tRNA recognition that prevent their cross-reactivity. Although the E. coli HisRS•tRNA pair is a good candidate for GCE, its use in C. crescentus is limited by the lack of established genetic selection methods and by the low transformation efficiency of C. crescentus. E. coli was genetically engineered to use a C. crescentus HisRS•tRNA pair. Super-folder green fluorescent protein (sfGFP) and chloramphenicol acetyltransferase (CAT) were used as reporters for read-through assays. A library of 313 ncAAs coupled with the sfGFP reporter system was employed to investigate the specificity of E. coli HisRS in vivo. A genomically modified E. coli strain (named MEOV1) was created. MEVO1 requires an active C. crescentus HisRS•tRNA pair for growth, and displays a similar doubling time as the parental E. coli strain. sfGFP- and CAT-based assays showed that the E. coli HisRS•tRNA pair is orthogonal in MEOV1 cells. A mutation in the anticodon loop of E. coli tRNA elevated its suppression efficiency by 2-fold. The C. crescentus HisRS•tRNA pair functionally complements an E. coli ΔhisS strain. The E. coli HisRS•tRNA is orthogonal in MEOV1 cells. E. coli tRNA is an efficient amber suppressor in MEOV1. We developed a platform that allows protein engineering of E. coli HisRS that should facilitate GCE in E. coli. This article is part of a Special Issue entitled "Biochemistry of Synthetic Biology - Recent Developments" Guest Editor: Dr. Ilka Heinemann and Dr. Patrick O'Donoghue.